Genome-wide analysis of NBS-LRR genes revealed contribution of disease resistance from Saccharum spontaneum to modern sugarcane cultivar - Jiang, Zhengjie; Zhao, Mengyu; Qin, Hongzhen; Li, Sicheng; Yang, Xiping (Frontiers in Plant Science, 2023)
Introduction During plant evolution, nucleotide-binding sites (NBS) and leucine-rich repeat (LRR) genes have made significant contributions to plant disease resistance. With many high-quality plant genomes sequenced, identification and comprehensive analyses of NBS-LRR genes at whole genome level are of great importance to understand and utilize them. Methods In this study, we identified the NBS-LRR genes of 23 representative species at whole genome level, and researches on NBS-LRR genes of four monocotyledonous grass species, Saccharum spontaneum, Saccharum officinarum, Sorghum bicolor and Miscanthus sinensis, were focused. Results and discussion We found that whole genome duplication, gene expansion, and allele loss could be factors affecting the number of NBS-LRR genes in the species, and whole genome duplication is likely to be the main cause of the number of NBS-LRR genes in sugarcane. Meanwhile, we also found a progressive trend of positive selection on NBS-LRR genes. These studies further elucidated the evolutionary pattern of NBS-LRR genes in plants. Transcriptome data from multiple sugarcane diseases revealed that more differentially expressed NBS-LRR genes were derived from S. spontaneum than from S. officinarum in modern sugarcane cultivars, and the proportion was significantly higher than the expected. This finding reveals that S. spontaneum has a greater contribution to disease resistance for modern sugarcane cultivars. In addition, we observed allelespecific expression of seven NBS-LRR genes under leaf scald, and 125 NBS-LRR genes responding to multiple diseases were identified. Finally, we built a plant NBS-LRR gene database to facilitate subsequent analysis and use of NBSLRR genes obtained here. In conclusion, this study complemented and completed the research of plant NBS-LRR genes, and discussed how NBS-LRR genes responding to sugarcane diseases, which provided a guide and genetic resources for further research and utilization of NBS-LRR genes.